Evaluation of seedling growth of Mungo-green beans on different substrates (Research, Society and Development, 2022)
The green Mungo bean is a crop rich in protein, vitamin B and iron. Because it is an economically accessible product and easy to cultivate in different climates, especially in dry areas, this culture can be implemented in small areas and does not require specialized labor. Being highly nutritious and easy to digest, Mungo beans can be consumed by people of any age group, regardless of any health problems. It has five vegetative phases V0, V1, V2, V3, V4 they are germination, emergence, primary leaves, first open composite leaf and third open composite leaf. In this way, we seek to evaluate three stages of growth of Mungo-green bean seedlings as the length of the root, length of the hypocotyl and days for emergence according to three different substrates, washed sand, organic compost and vermiculite. The substrates provide more adequate water management, the supply of nutrients in appropriate doses and times and the reduction of the occurrence of phytosanitary problems, among others. The experimental design adopted will be in random blocks. Each block will have 20 seedlings for each substrate, and in each cup it will have a different substrate, therefore, the assay will have the composition of three blocks of 20 cells each. The experiment obtained positive data in the organic compost substrate in relation to the development of roots and hypocotyl, in this way the vermiculite reached the best result in lifting the others, in terms of days for emergence.